Characterization of the friction and wear effects of graphene nanoparticles in oil on the ring/cylinder liner of internal combustion engine - Demirtas, Selman; Kaleli, Hakan; Khadem, Mahdi; Kim, Dae-Eun (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose This study aims to investigate the tribological characteristics of a Napier-type second piston ring against a cylinder liner in the presence of graphene nano-additives mixed into 5W40 fully synthetic engine oil. Design/methodology/approach Wear tests were carried out in the boundary lubrication condition using a reciprocating tribometer, and real engine tests were performed using a single spark ignition Honda GX 270 test engine for a duration of 75 h. Findings The experimental results of the tribometer tests revealed that the nano-additives formed a layer on the rubbed surfaces of both the piston ring and the cylinder liner. However, this layer was only formed at the top dead center of the cylinder liner during the engine tests. The accumulation of carbon (C) from the graphene was heavily detected on the rubbed surface of piston ring/cylinder liner, mixed with other additive elements such as Ca, Zn, S and P. Overall, the use of graphene nano-additives in engine oil was found to improve the frictional behavior in the boundary and mixed lubrication regimes. Abrasive wear was found to be the main mechanism occurring on the surface of both piston rings and cylinder liners. Originality/value Though many researchers have discussed the potential benefits of graphene as a nano-additive in oil to reduce the friction and wear in laboratory tests using tribometers, to date, no actual engine tests have been performed. In this paper, both tribometer and real engine tests were performed on a piston ring and cylinder liner using a fully formulated oil with and without graphene nano-additives in the boundary lubrication condition. It was found that a graphene nano-additive plays an active role in lowering the coefficient of friction and increasing surface protection and lubrication by forming a protective layer on the rubbing surfaces.
Keywords: Lubrication; Piston ring; Friction wear; Engine test; Graphene nanoparticles; TRIBOLOGICAL PROPERTIES; LUBRICANT ADDITIVES; PERFORMANCE; NANOFLUIDS; SURFACES; REDUCTION; SPHERES; Engineering